2005
DOI: 10.1002/cm.20103
|View full text |Cite
|
Sign up to set email alerts
|

Non‐centrosomal microtubule‐organising centres in cold‐treated cultured Drosophila cells

Abstract: In this paper we describe a new type of non-centrosomal microtubule-organising centre (MTOC), which is induced by cold treatment of certain cultured Drosophila cells and allows rapid reassembly of microtubule (MT) arrays. Prolonged cooling of two types of cultured Drosophila cells, muscle cells in primary culture and a wing imaginal disc cell line Cl.8+ results in disassembly of MT arrays and induces the formation of clusters of short MTs that have not been described before. Upon rewarming, the clusters are lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 44 publications
5
25
0
Order By: Relevance
“…At 10 min, MT foci were more numerous and assembled into an extensive interconnecting MT network throughout the cell ( Figure 6A, 10 min). By 15 min, S2 cells displayed a normal interphase array, having dispersed the MT foci that formed in the earlier time points ( Figure 6A, 15 min).Previous MT regrowth experiments using cultured fly cells described the appearance of unique MT foci similar to what we observed (Colombié et al, 2006;Cottam et al, 2006). Although individual MTs and foci form independently of interphase centrioles in S2 cells (our findings, Figure 6A), ␥-tubulin colocalizes with MT foci that assemble in cold- …”
supporting
confidence: 79%
“…At 10 min, MT foci were more numerous and assembled into an extensive interconnecting MT network throughout the cell ( Figure 6A, 10 min). By 15 min, S2 cells displayed a normal interphase array, having dispersed the MT foci that formed in the earlier time points ( Figure 6A, 15 min).Previous MT regrowth experiments using cultured fly cells described the appearance of unique MT foci similar to what we observed (Colombié et al, 2006;Cottam et al, 2006). Although individual MTs and foci form independently of interphase centrioles in S2 cells (our findings, Figure 6A), ␥-tubulin colocalizes with MT foci that assemble in cold- …”
supporting
confidence: 79%
“…The reorganization of the actin and MT cytoskeletons during myogenesis has long been observed in cell culture as individual myoblasts fuse into multinucleated myotubes (Bugnard et al, 2005;Cottam et al, 2006;Musa et al, 2003;Pizon et al, 2005;Tassin et al, 1985). Although the actin cytoskeleton has been shown to be…”
Section: Discussionmentioning
confidence: 99%
“…S3A,B in the supplementary material). γ-tubulin requires RacGAP for its localization to the nuclear periphery Studies in cultured myotubes have shown that γ-tubulin, a minusend anchoring protein essential for MT nucleation at the centrosome (Gunawardane et al, 2000;Stearns et al, 1991), may also be able to promote nucleation from non-centrosomal sites along the nuclear membrane and throughout the cytoplasm (Bugnard et al, 2005;Cottam et al, 2006;Musa et al, 2003). Based upon the previously defined role for RacGAP in MT organization during cell division, as well as our current findings that MT polarity in myotubes is altered in RacGAP and pav mutants (Fig.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations